2004
DOI: 10.1073/pnas.0405989102
|View full text |Cite|
|
Sign up to set email alerts
|

S -nitrosoprotein formation and localization in endothelial cells

Abstract: Protein S-nitrosation represents a recently described form of post-translational modification that is rapid and reversible. However, the analysis of protein S-nitrosation in situ has been difficult because of the absence of specific probes and the instability of cellular protein S -nitrosothiols. We developed a rapid and specific method for detecting endothelial S -nitrosoproteins patterned after the biotin switch method that involves thio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
109
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 131 publications
(115 citation statements)
references
References 35 publications
5
109
1
Order By: Relevance
“…To determine which pool is the primary target for nitrosative chemistry, the LMW and HMW fractions from lysates of sper/NO-exposed cells were separated by using filters (10,000-kDa cutoff). After treatment with 10 M (1,19,20). These results show that the mechanism responsible for RSNO formation is only slowly reversible and that the increase in RSNO levels ( (21), which in acellular systems are capable of nitrosative chemistry (8,9).…”
Section: •No Exposure Results Inmentioning
confidence: 71%
“…To determine which pool is the primary target for nitrosative chemistry, the LMW and HMW fractions from lysates of sper/NO-exposed cells were separated by using filters (10,000-kDa cutoff). After treatment with 10 M (1,19,20). These results show that the mechanism responsible for RSNO formation is only slowly reversible and that the increase in RSNO levels ( (21), which in acellular systems are capable of nitrosative chemistry (8,9).…”
Section: •No Exposure Results Inmentioning
confidence: 71%
“…This compartmentalization is beautifully depicted in animal system by caspase activation during apoptosis (Mannick et al, 2001). Using a combination of fluorescence labeling methods, elimination of functional mitochondria and electron transport inhibitors it was shown that S-nitrosothiol formation appears to be localized principally to mitochondria and that intact mitochondria are required for optimal S-nitrosothiol formation (Yang and Loscalzo, 2005). Also in another recent study using immuno gold electron microscopy, with anti-S-nitrosocysteine antibodies, it was shown that S-nitrosylated proteins were present in distinct cellular compartments such as endoplasmic reticulum and vesicular membrane structure near the Golgi complex (Greco et al, 2006).…”
Section: Compartmentalizationmentioning
confidence: 99%
“…This method involves blocking the free cysteines in the protein or protein mixture with the thio-specific methylthiolating agent MMTS, specific decomposition of nitrosothiols using ascorbate, which results in reduction of nitrosothiols to thiols, and labeling the newly formed free thiol groups with a sulfhydryl-specific biotinylating reagent biotin-HPDP. This method is followed by either immunoblotting with antibodies against biotin or Western blotting and mass spectrometry for identifying the S-nitrosylated proteins in various cell extracts, including brain extracts, endothelial cells, and mesangial cells ( Jaffrey et al, 2002;Kuncewicz et al, 2003;Martinez-Ruiz and Lamas, 2004;Lindermayr et al, 2005;Martinez-Ruiz et al, 2005;Yang and Loscalzo, 2005). Since our interest was to determine the sites of S-nitrosylation in a known protein rather than identifying the proteins that have undergone S-nitrosylation, we modified the biotin switch assay in the following fashion: after nitrosylation and following the biotin switch assay procedure, eNOS protein was digested by trypsin and peptide massmapping experiments were used to determine the sites of S-nitrosylation.…”
Section: Determination Of S-nitrosylation Sites In Enos Treated With mentioning
confidence: 99%